Berta Cáceres, Agency and Resistance: A Feminist-indigenous interpellation to the capital / life crisis - Muñoz Saavedra, Judith.; Ascencio Cortés, María Soledad.; Madrid Rossel, Zoila. (Institucio Alfons el Magnanim - Diputacio de Valencia, 2023)
This article explores the relationship between and the intersection of Feminist agencies and indigenous women’s resistance movement strategies in Mesoamerica by focusing on Honduran indigenous activist Berta Caceres Flores, who was murdered in 2016. Caceres’s speeches as leader of the Honduran Civic Council of Popular and Indigenous Organisations (COPINH) between 2009 and 2016 are analysed through the lens of three key topics: Agency; Resistance strategies; Grassroots-indigenous Feminism. The methodology used in this paper builds on Sociological Discourse Analysis (SDA) and highlights the structure of discourse based on categories such as the context of production and its interpretation as a social practice. The study’s findings lead to the idea that Caceres’ discursive position embodies the junction between indigenous resistance and Feminist agencies, which is to say the grassroots defence of land and body as a response to the capital-life crisis and the commodification of common goods. The paper also questions Neo-Liberalism’s hegemonic narrative as it showcases subjective proposals forming part of resistance to colonial capitalist power. These subjectivities are expressed in practices based on ‘commons’, care, reciprocity, community life linked to nature, and the priority given to life’s reproductive cycle
Berta Cáceres, agencia y resistencia: una interpelación feminista-indígena a la crisis capital/vida